Assessing grout imperfections in prestressed concrete using MWCNTs and temperature-magnetic response techniques - Heeyoung Lee; Sanggyu Park; Wonseok Chung (Case Studies in Construction Materials)
Unfilled grout inside steel ducts used in prestressed concrete bridges causes corrosion of the steel reinforcement within the grout. This research aimed to detect imperfections in prestressed concrete grout infused with multi-walled carbon nanotubes (MWCNTs) by utilizing Joule heating and measuring magnetic arena strength. Grout specimens containing MWCNTs were prepared with dimensions of ø100 mm × 200 mm. The grout satisfying rate and concentration of MWCNTs were used as test parameters. Joule heating experiments were performed, and magnetic arena measurements were obtained to investigate temperature variations and magnetic arena strength, respectively. The analysis revealed that grout mixed with 1.0 wt% MWCNT exhibited the largest temperature variation and magnetic arena strength, and these factors decreased with decreasing MWCNT concentration. The results confirm that detecting unfilled grout in steel ducts can be successfully achieved by measuring temperature variations and magnetic arena strength.